Peningkatan Akurasi Sensor GY-521 MPU-6050 dengan Metode Koreksi Faktor Drift - Fakhruddin Mangkusasmito; Dista Yoel Tadeus; Heru Winarno; Eko Winarno (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
GY-521 MPU-6050 Module is a core module MPU-6050, which is a 6 axis Motion Processing Unit. This sensor can be categorized as an Inertial Measurement Unit (IMU) sensor, which utilizes measurement systems such as gyroscopes and accelerometers to estimate the relative position, velocity, and acceleration of an object. A common accuracy problem in using IMU sensors, including the GY-521 MPU-6050, is the drifting phenomenon. This phenomenon results in a deviation between the actual conditions (position, angular velocity) and the sensor readings. Drift is caused by the accumulation of errors that arise from calculating the integral of the acceleration. This study proposes a drift error correction method at the sensor output using the calibration of the calculation of the average offset error sensor and the sensor fusion method between the information obtained from the gyroscope and accelerometer in the module, the tests were carried out using the Arduino Uno microcontroller. From the test results, it is found that the combination of the initial system calibration implementation and the use of the fusion sensor concept can provide better performance with the MSE analysis results for the roll position of 0.0029o and the pitch position of 0.0047o and the drifting error rate at the yaw angle position of 0 0082o / second or down 62.72%.